Efeito do laser de baixa potência na regeneração nervosa periférica, em ratos wistar com doença periodontal induzida - Malanotte, Jessica Aline (2018)
Periodontal disease is a chronic inflammatory condition of the teeth fixation structures, the proximity of the bacterial biofilm with periodontal vascularization facilitates the dissemination of bacteria, contributing to systemic inflammation, and may cause exacerbation of neuronal degeneration in the nervous lesions due to the intense inflammatory process. Studies report that low-power laser can improve the inflammatory condition in nerve lesions. Thus the objective of this study was to evaluate the effect of low power laser on peripheral nerve regeneration under the systemic inflammatory condition of periodontal disease. A total of 48 male rats were divided into 6 groups: control (GC); periodontal disease (GDP); nerve injury (GL); periodontal disease with nerve damage (GDPL); nerve damage and treatment (GLT); periodontal disease with nerve injury and treatment (GDPLT). On the 1st day of the experiment, ligation was performed around the lower first molars, which acted as a gingival irritant for 30 days. On the 15th day of the experiment, the nerve injury was performed by axonotmosis and the low power laser treatment started on the 18th day, performed for 2 weeks. The sciatic functional index (IFC) was evaluated, with subsequent euthanasia of all animals on the 30th day of the experiment. The sciatic nerve and right and left hemimandibula were collected for morphological, histological, radiographic and oxidative stress analysis. In the radiographic and histomorphometric analysis of the mandible, it was possible to confirm the induction of periodontal disease, in the results of the IFC, there was no statistical difference between the groups in the first pre-lesion evaluation, since the second evaluation, all groups presented a decrease in these values, which were maintained after treatment. In the histomorphometry of the nervous tissue there was no difference between the groups in the total nerve fibers (FN), in relation to the total of viable NF and greater than 4 micrometers, GC and GDP presented greater amount than GL and GDPL, in the fibers smaller than 4 μm all groups were similar. GC and GDP showed lower amounts of non-viable fibers. In relation to the diameters of the FN and myelin and axon sheath, GC and GDP presented larger diameters for the FN greater than 4μm, while in the smaller ones only 4μm for the BM there was difference, GC presented a larger diameter than GL and GDPL. All groups showed similar amounts of blood vessels and percentage of connective tissue. In the density of the cell nuclei, GC and GDP presented lower mean values than the other groups. In the morphology of the GDPL nervous tissue presented integral fibers of larger diameter while GLT and GDPLT larger and smaller diameters. In the antioxidant system, there was an increase in protein concentration, higher superoxide activity, and decreased glutathione transferase activity in the treated groups. Catalase and cholinesterase did not differ between groups, and lipoperoxidation was increased in the PD groups. In conclusion, the low power laser in the parameters used was not effective in increasing the nociceptive threshold, but it helped in the regeneration of the nerve fibers, although the inflammation in the place was still present, yet the treatment protected the cells against oxidative damages due to the increase of the superoxide and protein, however the decrease of glutathione S transferase demonstrates the inhibition of this stage of the antioxidant system.